KOMUNIKASI PEMASARAN DALAM PENJUALAN PROPERTI ELITEPRO DI TANGERANG - Julianti, Devi; Mirza, Mochammad; Jeffri, Suci Emelsi (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2024)
Nowadays, the development of various business fields is very rapid because of the increasingly advanced and developing development. The purpose of the rapid development of this era is to pamper and satisfy consumers so that the needs of consumers are met in today's modern lifestyle. One of the branches of the economy that is growing rapidly today is the property industry. The purpose of this study is to find out marketing communication in property sales at ElitePro Tangerang in an effort to increase sales in 2024 and to find out the obstacles faced by ElitePro Tangerang in an effort to increase property sales in 2024. This research method uses a descriptive research type with a qualitative approach. The results of this research are that ElitePro products are property agent services that help market secondary and primary units. The property prices offered by ElitePro are very diverse. In determining the location of the marketing place, ElitePro conducts research and analysis of regional trends that are viral or that are widely liked by its target market. ElitePro promotes the property through social media, advertising on the portal, placing banners, and following up customers. ElitePro has obstacles in marketing property, including the number of competitors engaged in the field of property agents, lack of speed in marketing properties that are going viral, lack of strategic property units, too high prices, expensive digital advertising costs, and lack of discipline in managing working time for marketing